PREPOSISI PADA KITAB DANIEL VERSI KING JAMES - Onthonie, Aisma Natalia; Pelealu, Hetty; Pamantung, Rina P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTPreposition is a word which is placed before a noun or pronoun. It shows the relationship between word and some other words in a sentence. In this study, the writer uses descriptive methods in this research. The data were collected by finding sentences containing prepositions and the writer underlines the sentence that has the prepositions. The writer classifies the data that have been found according to the concepts used. Data are taken from the entire Book of Daniel in the Bible which consists of 12 Article 357 verses. The writer analyzes the form and meaning by using the concept of Aarts and Aarts (1982) and Harman (1992). The result of this research shows that prepositions on the book of Daniel King James Version are found in terms of form and meaning. The forms are simple prepositions (one-word preposition) consist of : At, in, before, of, between, on, by, since, despite, until, during, up, from, with, whereas complex prepositions (multiword preposition) consist of : According to, in front of, as to, in spite of, because of , in terms of, by means of, on account of, by virtue of, on behalf of, in accordance with, out of, in addition of, with regard to. The meanings of the preposition that founded, consist of : refers to place, time, goals and objectives, source or origin, cause or reason, way, tool, inclusion, size, and circumstances.Keywords : Prepositions, Form and Meaning, The Book of Daniel King James Version.